Services for young people with attention deficit/hyperactivity disorder transitioning from child to adult mental health services: a national survey of mental health trusts in England. - Hall, Charlotte L.; Newell, Karen; Taylor, John; Sayal, Kapil; Hollis, Chris (Sage, 2015)
Transition from child to adult mental health services is considered to be a difficult process, particularly for individuals with neurodevelopmental disorders such as attention deficit/hyperactivity disorder (ADHD). This article presents results from a national survey of 36 mental health National Health Service (NHS) trusts across England, the findings indicate a lack of accurate data on the number of young people with ADHD transitioning to, and being seen by, adult services. Less than half of the trusts had a specialist adult ADHD service and in only a third of the trusts were there specific commissioning arrangements for adult ADHD. Half of the trusts reported that young people with ADHD were prematurely discharged from child and adolescent mental health services (CAMHS) because there were no suitable adult services. There was also a lack of written transition protocols, care pathways, commissioned services for adults with ADHD and inadequate information sharing between services. The findings advocate the need to provide a better transition service underpinned by clear, structured guidelines and protocols, routine data collection and information sharing across child and adult services. An increase in the commission of specialist adult ADHD clinics is needed to ensure individuals have access to appropriate support and care.